Prospective multicenter study of the efficacy and safety of cold forceps polypectomy for ≤ 6-mm non-ampullary duodenal low-grade adenomas - Kanzaki, Hiromitsu; Horii, Joichiro; Takenaka, Ryuta; Nakagawa, Hiroyuki; Matsueda, Kazuhiro; Tsuzuki, Takao; Kita, Masahide; Yamasaki, Yasushi; Tanaka, Takehiro; Iwamuro, Masaya; Kawano, Seiji; Kawahara, Yoshiro; Tomoda, Jun; Okada, Hiroyuki (Endoscopy International Open, 2022)
Background and study aims Because the endoscopic treatment for non-ampullary duodenal adenoma (NADA) has a non-negligible risk of adverse events (AEs), a safe and easy treatment for NADA is desirable. This was a multicenter prospective trial evaluating the efficacy and safety of cold forceps polypectomy (CFP) for diminutive NADAs.Patients and methods This study was prospectively conducted at six general hospitals and one university hospital. The inclusion criteria were histologic and endoscopic diagnosis of low-grade NADA measuring ≤ 6 mm. A second endoscopy was scheduled for 1 month after CFP. After confirmation of the success of CFP, 6-month and 12-month surveillance endoscopies were scheduled. The primary endpoint was the endoscopic and histologic disease disappearance rates at the 12-month endoscopy.Results Thirty-nine lesions from 38 patients were prospectively included. Median tumor size at enrollment was 5 mm (range 3–6 mm). There were four cases of remnant lesions at the second endoscopy, and the lesion disappearance rate of single CFP was 89.7 % (35 /39; 95 % confidence interval (CI), 76.9 %–97.9 %). In three cases, complete removal of the lesion was achieved with a single re-CFP, but one case required four repeat CFPs. The lesion disappearance rate at 12-month endoscopy was 97.4 % (38 /39; 95 %CI, 86.8 %–99.5 %). During the follow-up period, no AEs related to CFP were observed.Conclusions CFP for NADA ≤ 6 mm was safe and effective in this study. This common endoscopic method to remove lesions may be an option for treatment of diminutive NADAs.